Concussion Knowledge of Youth Sport Athletes, Coaches, and Parents: A Review - Kim, Sungwon; Connaughton, Daniel P; Leeman, Robert F; Lee, Jong Hoon (Journal of Amateur Sport, 2018)
Mild traumatic brain injury, commonly known as a concussion, has gained widespread public attention. Approximately 1.1 to 1.9 million children ≤18 years old suffer sport/recreation-related concussions in the U.S. annually. The purpose of this review was to assess research articles examining concussion knowledge of youth sport athletes, coaches and parents. Twenty-one articles published from 2009-2016 were selected. The results of this review suggest that most athletes, coaches, and parents had good knowledge regarding the definition of a concussion, common signs/symptoms, and complications from repeated concussions, while most stakeholders had moderate knowledge about the causes, prevalence, and return-to-play guidelines. However, the majority of respondents did not correctly identify the emotional signs/symptoms associated with concussions, and did not know that youth concussions should be managed more conservatively than adult concussions. Notable knowledge gaps were found among youth athletes and parents compared to coaches. Suggestions to improve these youth sport stakeholders’ concussion knowledge are provided.